Low Vancomycin MICs and Fecal Densities Reduce the Sensitivity of Screening Methods for Vancomycin Resistance in Enterococci - Wijesuriya, T.; Perry, P.; Pryce, T.; Boehm, J.; Kay, I.; Flexman, J.; Coombs, Geoffrey; Ingram, P. (American Society for Microbiology, 2014)
Active surveillance is part of a multifaceted approach used to prevent the spread of vancomycin-resistant enterococci (VRE). The impact of fecal density, the vancomycin MIC of the isolate, and the vancomycin concentration in liquid medium on test performance are uncertain. Using fecal specimens spiked with a collection of 18 VRE (predominantly vanB) with a wide vancomycin MIC range, we compared the performances of commercial chromogenic agars (CHROMagar VRE, chromID VRE, Brilliance VRE, and VRE Select) and 1 liquid medium (Enterococcosel enrichment broth) for VRE detection. The specificity of solid media was excellent; however, the sensitivity at 48 h varied from 78 to 94%. Screening using liquid medium was less sensitive than screening with solid media, particularly as the vancomycin content increased. Sensitivity declined (i) as the fecal VRE density decreased, (ii) when the media were assessed at 24 h (versus 48 h), and (iii) for isolates with a low vancomycin MIC (sensitivity, 25 to 75% versus 100% for isolates with vancomycin MIC of <16 mg/liter versus >32 mg/liter on solid medium using 10 6 CFU/ml of feces). Depending on local epidemiology and in particular VRE vancomycin MICs, the sensitivity of culture-based methods for VRE screening of stool or rectal specimens may be suboptimal, potentially facilitating secondary transmission.